Analysis of financial information requirements and implementation of a financial data management system - Olgun, Murat. (Thesis (M.A.)- Bogazici University. Institute for Graduate Studies in Social Sciences, 1994., 1994)
The requirements regarding the collection and use of financial information have been analyzed from a practical implementation perspective. Standard definitions and formulations 'of the theory of investment management constitute the basis for the study. The most important output of the study is a "Financial Data Management System" with functions for storing, processing, and reporting financial information for four main types of financial assets (common stocks, commodities, foreign currencies and bonds).
Keywords: Management information systems.; Portfolio management.; Investments.; Investment analysis.